Writing Exile. Issue 2 (3rd April 2019) - Rahimi, Atiq
ABSTRACT: Atiq Rahimi accepted the invitation to present his keynote Ecrire l'exile at the 2018 international workshop 'Refugees in Literature, Film, Art and Media: Perspective on the Past and Present' in Liverpool. His speech, closing the event, was accompanied by its translation, 'Writing Exile', prepared by the organiser, Lida Amiri. In his keynote, Rahimi artistically contemplates the perilous route of refuge, and the implications for writers of a life in exile. In his brief but poignant essay, Rahimi traces his personal experience walking from Afghanistan to Pakistan.